Benign and Malignant Breast Disease at Rwanda's First Public Cancer Referral Center. (23rd March 2016) - Pace, Lydia E.; Dusengimana, Jean-Marie V.; Hategekimana, Vedaste; Habineza, Hamissy; Bigirimana, Jean Bosco; Tapela, Neo; Mutumbira, Cadet; Mpanumusingo, Egide; Brock, Jane E.; Meserve, Emily; Uwumugambi, Alain; Dillon, Deborah; et al.
Abstract: Background: Breast cancer incidence is rising in low- and middle-income countries. Understanding the distribution of breast disease seen in clinical practice in such settings can guide early detection efforts and clinical algorithms, as well as support future monitoring of cancer detection rates and stage. Patients and Methods: We conducted a retrospective medical record review of 353 patients who presented to Butaro Cancer Center of Excellence in Rwanda with an undiagnosed breast concern during the first 18 months of the cancer program. Results: Eighty-two percent of patients presented with a breast mass. Of these, 55% were diagnosed with breast cancer and 36% were diagnosed with benign disease. Cancer rates were highest among women 50 years and older. Among all patients diagnosed with breast cancer, 20% had stage I or II disease at diagnosis, 46% had locally advanced (stage III) disease, and 31% had metastatic disease. Conclusion: After the launch of Rwanda's first public cancer referral center and breast clinic, cancer detection rates were high among patients presenting with an undiagnosed breast concern. These findings will provide initial data to allow monitoring of changes in the distribution of benign and malignant disease and of cancer stage as cancer awareness and services expand nationally. Abstract : After the launch of Rwanda's first public cancer referral center and breast clinic, cancer detection rates were high among patients presenting with an undiagnosed breast concern. These findings will provide initial data to allow monitoring of changes in the distribution of benign and malignant disease and of cancer stage as cancer awareness and services expand nationally.